2017
DOI: 10.1002/ams2.313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the smaller superior mesenteric vein sign for the detection of acute superior mesenteric artery occlusion

Abstract: AimsThe smaller superior mesenteric vein (SMV) sign is a well‐known computed tomography (CT) parameter for acute superior mesenteric artery (SMA) occlusion. This CT sign is potentially beneficial for the early diagnosis of acute SMA occlusion; however, few reports have documented this sign. The present study aimed to determine the accuracy of the smaller SMV sign for the detection of acute SMA occlusion.MethodsWe retrospectively reviewed CT images from 20 patients with acute SMA occlusion and 1,216 controls. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It has been reported that the diameters of the SMV are significantly narrowed and become smaller than the SMA in intestinal ischemic diseases such as SMA thrombosis or non-occlusive mesenteric ischemia (NOMI) [14,15]. It is called the 'smaller SMV sign'.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the diameters of the SMV are significantly narrowed and become smaller than the SMA in intestinal ischemic diseases such as SMA thrombosis or non-occlusive mesenteric ischemia (NOMI) [14,15]. It is called the 'smaller SMV sign'.…”
Section: Discussionmentioning
confidence: 99%
“…After contrast IV administration an abrupt interruption of luminal enhancement is seen in vessel occlusion. The SMV/SMA (SMV superior mesenteric vein) diameter ratio is measured at the level of the upper part of the kidney, a ratio ≥1 is considered normal, indicating the absence of a smaller SMV sign, while a ratio <1 has been reported indicated of acute SMA occlusion [41,42]. The sensitivity and specificity of the so-called "smaller SMV sign "have been reported at 70% and 99.2% respectively and it has been assessed in non-contrast images, advocating its utility in case of unsurpassable contraindications to the use of contrast agents [41].…”
Section: • Acute Arterial Mesenteric Ischemiamentioning
confidence: 99%
“…The SMV/SMA (SMV, superior mesenteric vein) diameter ratio is measured at the level of the upper part of the kidney; a ratio ≥ 1 is considered normal, indicating the absence of a smaller SMV sign, while a ratio < 1 is indicative of acute SMA occlusion [47,48]. The sensitivity and specificity of the so-called "smaller SMV sign" for the detection of acute SMA occlusion have been reported at 70% and 99.2%, respectively, and it has been assessed in non-contrast images, advocating its utility in case of unsurpassable contraindications to the use of contrast agents [47]. Atherosclerotic steno-occlusion is usually observed in older patients with a history of systemic vasculopathy, and the risk of AMI increases when a critical stenosis involves two of the three major visceral arteries (Figure 4).…”
Section: Acute Arterial Mesenteric Ischemiamentioning
confidence: 99%